Electrocardiographic evolution in Anderson-Fabry disease patients on and off specific therapy: a potential marker to study the therapeutic cardiac goal. (3rd October 2022) - Baldassarre, R; Ditaranto, R; Barlocco, F; Lillo, R; Re, F; Marchi, G; Parisi, V; Ferrrara, V; Di Nicola, F; Chiti, C; Gimeno Blanes, J R; Graziani, F; et al.
Abstract: Background: Anderson Fabry disease (AFD) is an X-linked lysosomal storage disorder leading to a deficiency in α-galactosidase A and globotriasylceramide (Gb3) deposition in different organs, including the heart. In AFD patients electrocardiogram (ECG) represents an important tool to detect cardiac involvement. AFD specific therapy (enzyme replacement or chaperon therapy) has shown to modify the natural history of the disease and to decrease Gb3 levels, but so far there are no data on its influence on ECG evolution. Purpose: To assess the progression of ECG features in AFD patients on and off specific disease therapy and to evaluate the potential role of ECG in studying the cardiac specific response to therapy. Methods: We recruited 170 patients with an established AFD diagnosis, ≥18 years old (64 males 38%, median age 46±15 years) in a multicentre study cohort. We analysed their ECG evolution for a median follow-up of 64±48 months in patients off (group A, N=63) and on (group B, N=107) specific therapy. Results: AFD patients off specific disease therapy (group A) had similar age at baseline compared to those on therapy (47±14 vs 44±12 years; p=0, 171), however significantly differed for males prevalence [13 (21%) vs 51 (48%); p≤0, 001], classic phenotype [36 (57%) vs 82 (77%); p<0, 001)] and maximal wall thickness [11±3 vs 13±4 mm; p≤0, 0001]. As regards ECG features at baseline, group A showed a lower prevalence of repolarization anomalies [16 (25%) vs 51 (48%), p=0, 005], left ventricular hypertrophy [14 (22%) vs 51 (48%), p=0, 001], pseudo necrosis [4 (6%) vs 18 (17%) vs, p≤0, 060] and short PR [2 (3%) vs 12 (11%), p=0.0845]. During the follow-up ECG progression was observed in 9 patients in group A (14%), characterized by the development of repolarization anomalies (N=5; 8%), incomplete right bundle block (N=4; 6%), shortening of PR interval (N=2; 3%), left ventricular hypertrophy (N=2; 3%), left atrial enlargement (N=2; 3%) and complete right bundle block (N=1; 2%). Differently, in group B an ECG evolution was observed in 31 patients (29%) characterized by the development of repolarization anomalies (N=19; 18%), left atrial enlargement (N=12; 12%), complete right bundle block (N=8; 8%), left anterior fascicular hemiblock (N=4; 4%), left bundle block (N=4, 4%) and left ventricular hypertrophy (N=3; 3%). Among patients off therapy we observed an improvement of ECG in 1 patient characterized by regression of repolarization anomalies, which could be explained with the presence of transient overload anomalies. Conclusion: In AFD patients off and on specific disease therapy, ECG evolution was detected in 14% and 29% respectively, consistently with the more advanced cardiac involvement in patients on therapy (higher prevalence of male sex, classic phenotype and higher maximum wall thickness). The fact that one third of the patients showed ECG changes progression despite being on specific disease therapy could be relevant to better defined the therapeutic cardiac goal. Funding Acknowledgement: Type of funding sources: None.